Everywhere is home’: the paradox of 'homing' and child upbringing among Nigerian-Chinese families in Guangzhou city (2020)
Africa–China relations are facilitating different flows and inducing mobilities that have produced Afro-Chinese families in Guangzhou, China. This article examines how Nigerian- Chinese couples construct and embrace contradictory notions of home, as well as how their child upbringing practices manifest this paradox. The article uses data from life history interviews, repeated visits and in social hangouts involving both Nigerian-Chinese couples and individual Nigerian men in interracial marriages. Whereas Nigerian men tend to feel less at home, owing to problems such as perceived Chinese identity exclusivity, the uncertainty of life, and their experiences of discrimination and racism, their Chinese spouses, as internal migrants themselves, also feel similarly unwelcome in Guangzhou. Furthermore, Nigerian- Chinese couples feel obligated to secure the futures of their Afro-Chinese children due to a suspicion that Chinese society may not accept them. The parenting styles, hopes and aspirations revealed by Nigerian-Chinese couples regarding their children show that they view home as an un-centred category.